Microstructural and Mössbauer Spectroscopy Studies of Mg1-x ZnxFe2O4x=0.5, 0.7 Nanoparticles. (24th July 2014) - Lin, Jinpei; He, Yun; Lin, Qing; Wang, Ruijun; Chen, Henian
Abstract : Zinc substituted magnesium ferrite M g 1 - x Z n x F e 2 O 4 ( x = 0.5, 0.7 ) powders have been prepared by a sol-gel autocombustion method. XRD patterns show that the specimens with x = 0 . 5 and 0.7 exhibit single-phase spinel structure, and more content of Zn in specimens is favorable for the synthesis of pure Mg-Zn ferrites. Room temperature Mössbauer spectra of M g 1 - x Z n x F e 2 O 4 annealed at 800°C display transition from ferrimagnetic behavior to super paramagnetic behavior with increase in zinc concentration. The Mössbauer spectras of Mg0.5 Zn0.5 Fe2 O4 annealed at different temperatures display the magnetic phase change of the ferrite particles.